PENGETAHUAN DAN SIKAP TERHADAP HIGIENE SANITASI PEDAGANG/PENJAMAH MAKANAN JAJANAN - Kristina Br Tarigan; Deli Syaputri; Risnawati Tanjung; Samuel Marganda Halomoan Manalu; Jessica Natalia Br Ginting (Poltekkes Kemenkes Medan, 2022)
Food is the most basic necessity of life and has the potential to be contaminated with pathogenic bacteria. Factors that affect the quality of food is the behavior of food handlers in the application of food hygiene and sanitation. Personal Hygiene is important because it can stop the spread of bacteria from traders and handlers who process food until the food is ready to be served. This study aims to determine the relationship between knowledge and the relationship between attitudes and hygiene and sanitation actions of traders/food handlers in Stabat Square 2022. This research uses an analytic type of research with a Cross Sectional design, which is a study in which variables including risk factors and variables including effects are observed. The sample taken from this research using Total Sampling is a sampling technique where if the total population is below 100 then it can be used as a sample. The total sample size is all 33 street food vendors/handlers. The results of the study show the value of knowledge with sanitation hygiene measures p value 0.02, attitudes with hygiene measures p value 0.02. The main conclusion of the study is that there is a relationship between knowledge and action and there is a relationship between attitudes and actions.